(untitled) (Development Service Industry Management, 2023)
Investment policy is shaped at various hierarchical levels and implemented through investment activity, which serves as a crucial driver of socio-economic system development at the macro-, meso-, and micro-levels. A comprehensive analysis of the essence of "investment activity" reveals a diversity of scientific interpretations, which can be grouped into several key approaches: process-based, resource-based, goal-oriented, institutional, and economic. Each of these offers a unique lens through which investment activity is conceptualized, highlighting its multifaceted nature. The author’s proposed definition synthesizes these approaches, placing a special emphasis on the strategic dimension of investment management. In this context, investment activity is defined as a system of purposeful and coherent actions involving the planning, organization, execution, and control of resource allocation into various entrepreneurial, production, and social ventures. These actions aim to generate economic returns, stimulate innovation, achieve societal outcomes, and fulfill strategic objectives over both short-term and long-term horizons. The strategic orientation of investment activity underscores its role in fostering sustainable growth and competitiveness in dynamic environments. At the enterprise level, effective investment activity management necessitates a holistic approach encompassing the development of an investment strategy, comprehensive planning, project evaluation and selection, practical implementation, and ongoing monitoring and control. Moreover, the investment process must be adaptable, involving regular reassessment and refinement of the strategy to respond to internal changes and external challenges. This integrated approach ensures that investment decisions are aligned with broader organizational goals and contribute meaningfully to overall economic and social progress.